(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2023)
An experiment was conducted with a simple lattice design with two replications to estimate the genetic variability in 62 soybean genotypes and 2 standard check varieties. The variability parameters such as mean, range of variation, genotypic and phenotypic coefficient of variation, heritability in the broad sense, genetic advance, and genetic advance as percentage of mean were estimated for 11 different traits. The values of the phenotypic coefficient of variation (PCV) were greater than the genotypic coefficient of variation (GCV) for all the traits, revealing the influence of environmental factors. The value of heritability was determined to be high for the traits such as grain yield, harvest index, number of seeds per pod, number of primary branches per plant, number of pods per plant and hundred seed weight. Indicating that the larger portion of total variation would be under genetic control and selection based on phenotypic levels would be useful for the improvement of these traits in soybean. High estimates of heritability together with high genetic advance as percentage of mean were recorded for grain yield, harvest index, number of seeds per pod, number of primary branches per plant, number of pods per plant and hundred seed weight, which may be attributed to the presence of additive gene action and had high selective value. Thus, selection pressure could successfully be applied to these traits for soybean improvement programs. Int. J. Agril. Res. Innov. Tech. 12(2): 14-17, December 2022